1993
DOI: 10.1021/jm00067a003
|View full text |Cite
|
Sign up to set email alerts
|

Novel 2-substituted tetrahydro-3H-benz[e]indolamines: highly potent and selective agonists acting at the 5-HT1A receptor as possible anxiolytics and antidepressants

Abstract: The synthesis of (+)-(R)-2-cyano-N,N-dipropyl-8-amino-6,7,8,9-tetrahydro-3H- benz[e]indole [(R)-14, U92016A], a potent 5-HT1A agonist, and related analogs is described. In vitro binding studies show that the (R)-enantiomers of this series possess the highest potency for the 5-HT1A receptor. In vivo hypothermia correlates with this, with the (R)-enantiomers causing a greater temperature drop than the (S)-enantiomers. The most active compound in 5-HT1A binding and in the in vivo models was (R)-14, which was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 11 publications
0
11
0
1
Order By: Relevance
“…The enantiomers and racemates of 27 and 28 were evaluated for their affinities to the 5-HT 1A receptor sites and in agreement with the biochemical and behavioural data. The Also, substitution at the C-2 of the pyrrole with a carboxamide (34) or cyano UH92016A -35 function is favourable for 5-HT 1A affinity [54]. In fact, compound (+)-…”
Section: -Htmentioning
confidence: 99%
“…The enantiomers and racemates of 27 and 28 were evaluated for their affinities to the 5-HT 1A receptor sites and in agreement with the biochemical and behavioural data. The Also, substitution at the C-2 of the pyrrole with a carboxamide (34) or cyano UH92016A -35 function is favourable for 5-HT 1A affinity [54]. In fact, compound (+)-…”
Section: -Htmentioning
confidence: 99%
“…Extrapolating dose from animal to man is difficult. For example, the published K I value for buspirone against D2 is some tenfold higher in the rat [19] than in humans [20], although this does not necessarily mean the same is true in any other small mammal species. The pharmacokinetics and binding affinity of buspirone for the D 2 and 5HT 1A receptors in the ferret are unknown and may be very different from those in humans.…”
Section: Discussionmentioning
confidence: 97%
“…The resulting precipitate was filtered off, and the solution was evaporated to a residue of 25 mg (94%) of pure product. The fumarate salt was prepared and recrystallized from methanol/diethyl ether: mp 188-191 °C (fumarate); NMR (300 MHz, CDCI3) 0.90 (t, 6H), 1.50 (sxt, 4H), 1.65 (m, 1H), 2.05 (br s, 1H), 2.50 (s, 3H), 2.55 (t, 4H), 2.93 (dd, 2H), 3.0-3.2 (m, 2H), 3.52 (m, 1H), 6.85 (d, J = 8.3 Hz, 1H), 6.87 (s, 1H), 7.08 (d, J = 8.3 Hz, 1H), 7.9 (br s, 1H); MS m/e 284 (M+, 50), 184 (100), 255 (68), 157 (36), 168 (11). Anal.…”
Section: Methodsmentioning
confidence: 99%
“…Compounds 9 and 10 were less potent. In the same article it was found that the isosteric (to 4) 8-(dipropylamino)-6,7,8,9-tetrahydrobenz[g]indole (11) and analogs were inactive at 5-HTia receptors. Furthermore, the IV-formylindoline 12, which is easily superimposed on 5 and thus would seem to mimic 5, was almost inactive at 5-HTia receptors.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation